1984
DOI: 10.1111/j.1751-1097.1984.tb08392.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Dependence of Hypericin‐induced Phototoxicity to Emt6 Mouse Mammary Carcinoma Cells

Abstract: The photodynamic effect of hypericin on EMT6 mouse mammary carcinoma cells was investigated in virro under aerobic and hypoxic conditions. Under aerobic conditions, hypericin-induced photocytotoxicity was dose dependent within a 1-50 p M range. Under hypoxic conditions, cells were resistant to hypericin-induced phototoxicity. In the dark, no cytotoxicity was observed at any hypericin concentration tested either aerobically or hypoxically. Cellular accumulation of hypericin, examined by chemical extraction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 17 publications
3
51
0
Order By: Relevance
“…Hypoxic tumor cells have been shown to be more resistant to many conventional therapies than their normoxic counterparts. Since molecular oxygen is a prerequisite for ROS generation and since PDT itself also induces oxygen consumption during light irradiation, hypoxia has been reported to lead to tumor resistance to the phototoxic effects of PDT . On the contrary, 45IR exhibited significant phototoxicity against MKN‐45‐luc cells even under low oxygen tension.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic tumor cells have been shown to be more resistant to many conventional therapies than their normoxic counterparts. Since molecular oxygen is a prerequisite for ROS generation and since PDT itself also induces oxygen consumption during light irradiation, hypoxia has been reported to lead to tumor resistance to the phototoxic effects of PDT . On the contrary, 45IR exhibited significant phototoxicity against MKN‐45‐luc cells even under low oxygen tension.…”
Section: Discussionmentioning
confidence: 99%
“…If the extent of diffusion of oxygen from surrounding tissue or blood vessels does not match the loss of oxygen during PDT, the net result is a decrease of oxygen in the vicinity of the photosensitizer, and as a consequence, a loss of its PDT efficacy. Because hypericin phototoxicity is oxygen dependent,33 which is mediated predominantly via the production of singlet oxygen,34 it is likely that oxygen consumption during light irradiation35 renders tumor cells less sensitive to the direct photodynamic action of hypericin.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen dependence was used as a critical test to discriminate Type I from Type II. Thomas and Pardini 69 investigated the effects of oxygen on the hypericin‐induced photosensitization of EMT6 mouse mammary carcinoma cells under both aerobic and hypoxic conditions and observed that the hypericinphotoinduced cell killing was mediated by an oxygen‐dependent mechanism (Type II), rather than by an oxygen‐independent process (Type I). Recently Fehr et al 70 have studied the role of oxygen in the photoinactivation of viruses by hypericin and have concluded that both Type I and Type II are involved in antiviral photoinactivation, and the ratio of Type I to Type II may depend on the intensity of irradiation used.…”
Section: Molecular Photosensitization Mechanism and Oxygen Dependencementioning
confidence: 99%
“…A 1000‐fold photopotentiation has been observed with MPTK‐6 neoplastic cells using hypericin as a photosensitizer 74 . Hypericin was also demonstrated to exert potent photoxicity on EMT‐6 cells at a non‐dark toxic dose 69 …”
Section: Pdt Application (Anticancer)mentioning
confidence: 99%